Needs Analysis of English for Specific Purposes at Food Beverage Emersia Hotel Bandar Lampung - Fajar Riyantika; Robby Yuli Endra; Threesa Afrulli; Ayu Kartika Puspa (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2020)
The objective of this study is to reveal the language need for hotel staffs in developing English skills based on needs analysis. The participants of this study are three males and two females’ senior staffs. The interview as the instrument to get primary data. The result of this study indicates that speaking and listening are the major need of the staffs. The staffs mostly need speaking and listening skill. Speaking is the most frequently used oral communication to communicate with guests. Speaking also the language functions needed were in greeting, offering menu, asking for the customer's needs or orders, confirmation, dealing with billing, apologizing or dealing with complaining, etc. In addition, some problems are found in listening like listening to accents and dialects. The staffs realize that the accent, the dialect, and the intonation of the guests can have a massive impact of their communication. Therefore, listening is also very needed in their work because listening skill is also needed by the staffs since speaking and listening are interrelated skills. Based on the findings, one suggestion was proposed: to prepare a language training program to improve the English language skills of the staff.